Manajemen Bisnis Online For Beginners - Widyaningsih, Bekti; Hakim, Ahmad Khusnul (Universitas KH. A. Wahab Hasbullah, 2022)
This study discusses online business management, namely the understanding of management itself followed by the functions of management as well as the characteristics of a good manager as well as various types of management. This study aims to determine the flow of buying and selling information systems from online sellers via the internet in Jombang district, making it easier for consumers to access what we market online via the internet, knowing the shortcomings of how to run a business for a beginner. The research analysis used is a qualitative case study approach, which is a strategy or method that is powerful enough to examine in depth the case to be studied. The results of this study obtained indicators of the application of online business for beginners, namely the expansion of the marketplace, fast access to information, and being able to approach good relationships with customers.